‘Never trust a philologist’: C.S. Lewis, J.R.R. Tolkien, and the place of philology in English Studies - Horobin, S (Oxford University Press, 2024)
This article brings to light seven poems by C.S. Lewis that have never been published before. These poems, composed during the 1920s, form part of a lengthy campaign against the study of philology at Oxford, and specifically against its most eminent exponent, H.C. Wyld. Drawing on entries in his diary and personal correspondence, the article shows how Lewis’s antipathy for the subject grew out of his undergraduate studies, his frustration with Wyld’s published scholarship and prescriptive attitude towards language study, as well as a dislike of the man and his lecturing style. It was the appointment of J.R.R. Tolkien to the Rawlinson and Bosworth Professorship of Anglo-Saxon in 1925, and their subsequent friendship, that was to convert Lewis to the study of philology and convince him of its centrality to the discipline of English Studies. The remainder of the article describes how the two men engineered revisions to the Oxford English syllabus, which resulted in a much more prominent role for philology, at the expense of nineteenth-century literature.